Developing the Framework for a Green Constitution: Strengthening Environmental Protection Initiatives in Indonesia - Hakim Rianta, Muhammad; Imron, Pradnya Kayla Ali; Danjuma, Ibrahim (Faculty of Law Universitas Negeri Semarang, 2023)
The current global environmental crisis occurs due to various factors, such as failed policies, destructive technologies, and lack of political commitment. To address these issues, the green constitution approach has emerged as an effective solution. However, Indonesia has not fully implemented the concept of a green constitution. This research uses a normative legal research method with comparative, conceptual, and statutory approaches. Data is obtained from a literature study of national and international regulations, books, articles, and scientific journals. Through a comparative study with Ecuador and France, the results show that Indonesia has the potential to integrate environmental principles that have been integrated into the constitutions of these countries. Ecuador, often referred to as